An E-learning website for the College of Computer Science - Hintay, Mari Timothy; Acenas, Annabelle C.;Fabula, Elmer (Manila : National University, 2010)
Technological advancements are the results of man's persistence to improve not only his environment but also his development as well. The primary objective of the study is to develop an E-learning website for the College of Computer Studies of National University. The study will focus on developing an E-learning website which will provide efficient and useful source of knowledge, accurate, organize and easiest way of studying lessons.
Title page -- Approval page -- Acknowledgement -- Abstract -- Table of contents -- List of appendices -- Chapter I: The problem and its background -- Chapter II: Review of related literature and studies -- Chapter III: Research methodology -- Chapter IV: Presentation, analysis and interpretation of data -- Chapter V: Summary, conclusion and recommendation.
Includes bibliographical references.